Analysis of hygroscopic cloud seeding materials using the Korea Cloud Physics Experimental Chamber (K-CPEC): a case study for powder-type sodium chloride and calcium chloride - B.-Y. Kim; M. Belorid; J. W. Cha; Y. Kim; S. Kim (Atmospheric Measurement Techniques)
In this study, we analyzed the particle characteristics and cloud droplet growth properties of NaCl and CaCl2, which are powder-type hygroscopic materials applied in cloud seeding experiments, using the Korea Cloud Physics Experimental Chamber (K-CPEC) facility at the Korea Meteorological Administration/National Institute of Meteorological Sciences (KMA/NIMS) in South Korea. The aerosol chamber (volume 28.3 m3) enabled the observation of particle characteristics in an extremely dry environment (relative humidity (RH) < 1 %) that was clean enough to ignore the influence of background aerosols. The cloud chamber featured a double-structure design, with an outer (130 m3) and inner (22.4 m3) chamber. The inner chamber allowed the precise control of air pressure (1013.25–30 hPa) and wall temperature (−70–60 °C), facilitating cloud droplet growth through quasi-adiabatic expansion. In this study, a cloud chamber experiment was conducted to simulate both wet adiabatic and stable environmental lapse rate conditions. The experiments were initiated at low RH (< 60 %), and the variations in the cloud droplet concentration and diameter were observed as RH increased, leading to supersaturation (RH > 100 %) and subsequent cloud droplet formation. NaCl and CaCl2 powders showed distinct particle growth behaviors owing to the differences in their deliquescence and hygroscopicity. The rate of cloud droplet formation in the NaCl powder experiments was slower than that for CaCl2; however, the mean and maximum droplet diameters were approximately 2–3 and 10–20 µm larger, respectively. The particle diameter, including aerosols and droplets, varied from 1 to 90 µm, and large cloud droplets (30–50 µm) that served as the basis for drizzle embryo formation were also observed. Our study provides valuable insights for the development of new seeding materials and advanced cloud seeding experiments.